Sulfur-modified iron-based biochar slow-release composite material as well as preparation method and application thereof
By using rice straw as a biochar raw material, loading iron salts and modifying it with sodium sulfide, a sulfur-modified iron-based biochar slow-release composite material was prepared, which solved the inactivation and tailing phenomena of nano zero-valent iron in treating TCE pollution. problem, achieving long-term removal and low-cost repair of TCE.
Patent Information
- Application Number
- CN202411438192.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-21
AI Technical Summary
When dealing with trichloroethylene (TCE) pollution in soil and groundwater, nano zero-valent iron (nZVI) is prone to agglomeration and inactivation, difficult to separate and reuse, and cannot complete the removal of TCE in one go. , resulting in tailing phenomenon and high repair costs.
Agricultural waste rice straw was used as biochar raw material, loaded with iron salts, and sulfur-modified iron-based biochar slow-release composite materials were prepared through sodium sulfide modification and one-step carbon reduction method. This material achieves long-term removal of TCE through the loading of nanoscale zero-valent iron and the porous structure of biochar.
Under mild reaction conditions, this material is simple to operate and low-cost, and can effectively remove TCE from groundwater for a long time, significantly reducing repair costs and extending the service life of composite materials.
Smart Images

Figure CN119327419A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of environmental pollution remediation, and in particular to a sulfur-modified iron-based biochar slow-release composite material and a preparation method and application thereof. Background Art
[0002] Trichloroethylene (TCE), as a typical chlorinated hydrocarbon (CAHs), has been widely used in the production of insecticides, pesticides, coatings and metal degreasers. CAHs pollution is spread all over the world, and its three-way effects and genotoxicity pose a major threat to human health and the ecological environment. The widespread use of TCE in many industrial sectors and its inevitable emissions have caused soil and groundwater pollution. TCE belongs to volatile organic compounds (VOCs), and the contaminated vapor evaporates from the groundwater and enters the overlying buildings (vapor intrusion), posing a potential long-term risk to the human health of residents. At the same time, low concentrations of TCE can damage the liver and even produce carcinogenic properties in animals. In addition, since TCE is not affected by natural degradation, they can easily accumulate in the environment and even transform into more toxic vinyl chloride, posing a continuous danger to the ecosystem. Therefore, effective reduction of TCE is very necessary to reduce the risk level.
[0003] In recent years, many physical-chemical-biological methods have been reported for treating TCE in soil and groundwater, such as physical adsorption, chemical reduction, chemical oxidation, biodegradation, and zero-valent iron reduction. Among them, nano-zero-valent iron (nZVI) reduction is considered to be one of the most promising methods for TCE treatment. nZVI is an active metal. 0 (Fe 2+ / Fe) standard electrode potential is -0.44V, with strong reducing ability, and can release electrons when oxidized, so it can quickly and directly degrade TCE. At present, many researchers have studied the environmental applications of nZVI and reported several field applications in groundwater remediation. However, there are still many challenges that limit the widespread application of nZVI. For example, nZVI is prone to agglomeration and inactivation during operation, and it is difficult to separate and reuse after degradation is completed. It may be released into the environment, thus posing risks to the ecosystem. In order to overcome this shortcoming, many researchers have paid attention to introducing nZVI into carbon materials or porous membranes. Compared with other carriers of metal nanoparticles, the introduction of carbon materials can form a galvanic effect with nano zero-valent iron, enhance the electron loss ability of nano zero-valent iron, thereby improving the reaction activity and enhancing the service life of nano zero-valent iron; and the introduction of membrane materials can significantly improve the loading capacity of nZVI, improve the accessibility of reactants to active sites, and greatly reduce the potential loss of nZVI into the environment.
[0004] However, in actual remediation projects, due to the low solubility, high density and strong hydrophobicity of TCE, it is easy to form a heavy non-aqueous phase liquid (DNAPLs) pollution plume in the pollution source area, so no matter how much remediation material is added, it is impossible to complete the removal of TCE in one go, and the tailing phenomenon is difficult to avoid. At the same time, whether it is carbon material-loaded nZVI composite materials or membrane material-loaded nZVI composite materials, there is no selective reduction during the remediation process, and a large amount of remediation materials are wasted in side reactions with other media. The conversion of TCE in the solid-liquid-gas three phases makes it difficult to see the end of the tailing phenomenon of pollution removal, and in order to meet the remediation standards of TCE, a large amount of remediation materials have to be continuously added. The expensive remediation cost caused by this is obviously unacceptable. Therefore, it is particularly important to develop efficient slow-release reduction remediation materials for CAHs pollutants represented by TCE in soil and groundwater. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a sulfur-modified iron-based biochar slow-release composite material and its preparation method and application. The sulfur-modified iron-based biochar slow-release composite material prepared by the present invention uses agricultural waste rice straw as the biochar raw material to load iron salt, then uses sodium sulfide to modify it, and finally prepares the sulfur-modified iron-based biochar slow-release composite material by a one-step carbon reduction method. The sulfur-modified iron-based biochar slow-release composite material obtained by the present invention has a long-term removal effect on TCE in groundwater. The reaction conditions of the present invention are mild, the operation is convenient, the raw material cost is low, and the CAHs pollutants represented by TCE can be removed greenly and effectively for a long time, and it has huge potential application prospects in soil-groundwater pollution remediation projects.
[0006] The technical solution of the present invention to solve the above technical problems is as follows:
[0007] The first object of the present invention is to provide a method for preparing a sulfur-modified iron-based biochar slow-release composite material, comprising the following steps:
[0008] (1) washing, drying, grinding and sieving agricultural waste in sequence to obtain biomass material powder; shaking the biomass material powder in an iron salt solution to obtain iron-loaded biomass material powder;
[0009] (2) immersing the iron-loaded biomass material powder in a sodium acetate solution, adding acetic acid and sodium sulfide solution to obtain sulfur-modified iron-loaded biomass powder;
[0010] (3) The sulfur-modified iron-loaded biomass powder is prepared into sulfur-modified iron-based biochar by a one-step carbon reduction method, that is, a sulfur-modified iron-based biochar slow-release composite material.
[0011] The beneficial effects of the present invention are:
[0012] (1) The present invention uses agricultural waste, which is an abundant source, and increases the reduction point of the sulfur-modified iron-based biochar slow-release composite material by loading it with nano-zero-valent iron, which is beneficial to the reduction and dechlorination of chlorinated hydrocarbons; the nano-zero-valent iron is evenly dispersed through the porous structure of the biochar, which avoids the agglomeration of the nano-zero-valent iron and increases the reduction potential; based on the good adsorption and conductivity of the biochar material, the capture capacity of the target pollutants and the electron transfer and utilization efficiency are improved; through the modification of Na2S, FeS is doped into the nano-zero-valent iron particles, which increases the conductivity of the nano-zero-valent iron surface after oxidation, prolongs the reduction time of the composite material, and plays a slow-release role.
[0013] (2) The load treatment conditions of the present invention are simple, and the biochar pyrolysis operation is convenient. Not only is the material preparation cost low, but the technology promotion is also easy. At the same time, verification experiments have proved that the present invention can effectively remove chlorinated hydrocarbons in groundwater over a long period of time, and has certain application prospects.
[0014] Furthermore, the agricultural waste may be at least one of rice straw, rice husk, corn straw, wheat straw, and cow dung.
[0015] Based on the above technical solution, the present invention can also be improved as follows.
[0016] Furthermore, the concentration of the iron salt solution is 0.05 mol / L to 1.0 mol / L; the iron salt in the iron salt solution is at least one of a trivalent iron salt and a divalent iron salt.
[0017] Preferably, the trivalent iron salt may be FeCl3·6H2O, Fe(NO3)3·9H2O; the divalent iron salt is FeSO4·7H2O.
[0018] Furthermore, in step (1), the ratio of the biomass material powder to the iron salt in the iron salt solution is 1 g: (0.5×10 -3 ~0.03)mol.
[0019] Furthermore, the usage ratio of the iron salt-loaded biomass material powder, the sodium acetate solution, the acetic acid solution, and the sodium sulfide solution is 1 g: (100-500) mL: (0.1-0.4) mL: (0.1-1.0) mL.
[0020] Furthermore, the concentration of the sodium acetate solution is 1 g / L to 5 g / L; the acetic acid solution is a high-grade pure acetic acid reagent with a mass fraction of 36% to 38%; and the concentration of the sodium sulfide solution is 0.05 mol / L to 0.20 mol / L.
[0021] Furthermore, the one-step carbon reduction method is specifically as follows: placing the sulfur-modified iron-loaded biomass powder in a tubular furnace into which high-purity nitrogen is continuously introduced, heating it and then keeping it warm, and then naturally cooling it to room temperature to obtain a sulfur-modified iron-based biochar slow-release composite material.
[0022] The beneficial effect of adopting the above further scheme is that the present invention prepares the sulfur-modified iron-based biochar slow-release composite material by a one-step method, the method is simple, and is conducive to the mass production of the material.
[0023] Furthermore, the heating rate is 4°C / min to 6°C / min, the temperature after heating is 800°C to 900°C, and the insulation time is 1h to 4h.
[0024] Furthermore, the flow rate of the high-purity nitrogen is 60 mL / min to 90 mL / min.
[0025] The second object of the present invention is to provide a sulfur-modified iron-based biochar slow-release composite material.
[0026] The beneficial effects of the present invention are as follows: the agricultural waste such as agricultural straw used in the sulfur-modified iron-based biochar slow-release composite material of the present invention is abundant in source, the loading treatment conditions are simple, the biochar pyrolysis operation is convenient, not only the material preparation cost is low, but also the technology is easy to promote. The present invention also provides a way to process rice straw resources, which is conducive to the comprehensive utilization of straw.
[0027] The third object of the present invention is to provide an application of a sulfur-modified iron-based biochar slow-release composite material, and to use the sulfur-modified iron-based biochar slow-release composite material for removing trichloroethylene from groundwater.
[0028] The beneficial effect of the present invention is that the sulfur-modified iron-based biochar slow-release composite material provided by the present invention can efficiently remove trichloroethylene in groundwater. At the same time, experiments have proved that after a soaking reaction of up to 195 days, the sulfur-modified iron-based biochar slow-release composite material prepared by the present invention still has a very high trichloroethylene removal efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is an appearance diagram of the sulfur-modified iron-based biochar slow-release composite material of Example 1 of the present invention;
[0030] Figure 2 This is a scanning electron microscope image of the sulfur-modified iron-based biochar slow-release composite material of Example 1 of the present invention;
[0031] Figure 3 This is the XRD spectrum of the sulfur-modified iron-based biochar slow-release composite material of Example 1 of the present invention;
[0032] Figure 4 This is a shake flask experiment diagram for removing TCE in Experimental Example 2 of the present invention;
[0033] Figure 5 This is an analysis diagram of the removal effect of different materials on TCE in Experimental Example 2 of the present invention;
[0034] Figure 6 This is a diagram showing the removal effect of trichloroethylene in aqueous solution by the sulfur-modified iron-based biochar slow-release composite material before and after aging in Example 1 of the present invention. DETAILED DESCRIPTION
[0035] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific technology or conditions are specified in the embodiments, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased through regular channels.
[0036] Example 1: Preparation of sulfur-modified iron-based biochar slow-release composite material
[0037] (1) collecting rice straw, washing and drying, grinding by machine, passing through a 100-mesh sieve, and mixing uniformly to obtain rice straw powder;
[0038] (2) immersing rice straw powder in 0.3 mol / L FeCl3·6H2O solution, shaking horizontally at 180 prm for 24 h, filtering (the dosage ratio of rice straw powder: FeCl3·6H2O solution is 1 g: 30 mL), and drying in an oven at 80°C to obtain iron-loaded straw powder;
[0039] (3) The iron-loaded straw powder was immersed in a 2 g / L sodium acetate solution, placed in an anaerobic glove box, and firstly a 36% to 38% mass fraction of high-grade pure acetic acid reagent was added dropwise, and then a 0.1 mol / L Na2S·9H2O solution was added dropwise (the dosage ratio of iron salt-loaded biomass material powder: sodium acetate solution: acetic acid solution: Na2S·9H2O solution was 1 g: 250 mL: 0.2 mL: 1 mL), and then the mixture was shaken and allowed to stand for 1 h, filtered, and dried in an oven at 80°C to obtain sulfur-modified iron-loaded straw powder;
[0040] (4) The sulfur-modified iron-loaded straw powder was placed in a tubular furnace into which high-purity nitrogen was continuously introduced. The nitrogen flow rate was set to 80 mL / min. The temperature of the tubular furnace was set to a heating rate of 5 °C / min and raised to 800 °C. The insulation time was 2 h, and then the powder was naturally cooled to room temperature to obtain sulfur-modified iron-based biochar. The sulfur-modified iron-based biochar was placed in an anaerobic glove box, quickly ground and sieved through a 200-mesh sieve to obtain a finished sulfur-modified iron-based biochar composite material.
[0041] Embodiment 2-9:
[0042] The difference between Example 2-9 and Example 1 is only that the concentration of the iron salt and the ratio of the biomass raw material to the iron salt solution in step (2) are different, and the remaining raw materials and steps are the same as those in Example 1, as shown in Table 1 below:
[0043] Table 1
[0044]
[0045] Embodiment 10-18:
[0046] The difference between Examples 10-18 and Example 1 is only that the concentration of the sodium acetate solution, the concentration of the Na2S·9H2O solution and the amount of acetic acid added in step (3) are different, and the remaining raw materials and steps are the same as those in Example 1, as shown in Table 2 below:
[0047] Table 2
[0048]
[0049] Embodiment 19-25:
[0050] The difference between Examples 19-25 and Example 1 is only that the pyrolysis parameters in step (4) are different, and the remaining raw materials and steps are the same as those in Example 1, as shown in Table 3 below:
[0051] Table 3
[0052]
[0053]
[0054] Comparative Example 1: Preparation of rice straw biochar
[0055] The difference between this comparative example and Example 1 is that the modification of step (3) of Example 1 is not performed, and the remaining raw materials and steps are the same as those of Example 1, as shown below:
[0056] (1) collecting rice straw, washing and drying, grinding by machine, passing through a 100-mesh sieve, and mixing uniformly to obtain rice straw powder;
[0057] (2) The rice straw powder was placed in a tubular furnace into which high-purity nitrogen was continuously introduced. The nitrogen flow rate was set to 80 mL / min. The temperature of the tubular furnace was set to rise to 800 °C at a heating rate of 5 °C / min. The temperature was kept at this temperature for 2 h and then naturally cooled to room temperature to obtain rice straw biochar. The rice straw biochar was placed in an anaerobic glove box, quickly ground and sieved through a 200-mesh sieve to obtain the finished rice straw biochar.
[0058] Comparative Example 2: Original Rice Straw
[0059] This comparative example is the same original rice straw used before preparing the materials in the examples.
[0060] Test example:
[0061] 1. Microscopic characterization and performance analysis of sulfur-modified iron-based biochar slow-release composite materials
[0062] For example Figure 1 The sulfur-modified iron-based biochar slow-release composite material prepared in Example 1 was tested by scanning electron microscopy (Merlin; Zeiss, Germany) and X-ray diffractometer (D / max-2500 / PC; Rigaku Group, Japan) was used for XRD analysis. The SEM and XRD results are shown in FIG. Figure 2 , Figure 3 shown.
[0063] Depend on Figure 2 , Figure 3 We can get:
[0064] Figure 2 This is a SEM image of the sulfur-modified iron-based biochar slow-release composite material of Example 1. It can be seen from the image that the iron-based particles are evenly distributed on the surface of the biochar without obvious aggregation.
[0065] Figure 3 is the XRD pattern of the sulfur-modified iron-based biochar slow-release composite material of Example 1. Figure 3 It can be seen that the sulfur-modified iron-based biochar slow-release composite material was successfully synthesized. The material retains a broad amorphous carbon peak at around 22°, which may be the microcrystalline structure and disordered graphite layer formed during the pyrolysis of biomass. The most obvious diffraction peaks in the iron-based biochar are 44.352°, 64.526° and 81.654°, corresponding to the (110), (200) and (211) crystal planes of the Fe standard card (PDF No.85-1410), indicating that zero-valent iron particles were successfully generated after pyrolysis reduction of the iron-based biochar. At the same time, the most frequent diffraction peaks are those of FeS, with diffraction peaks appearing at 29.934°, 33.669°, 43.179°, 47.145°, 52.306°, 53.145°, 63.226° and 70.792°, corresponding to the (110), (112), (114), (211), (213), (300), (008) and (224) crystal planes of the FeS standard card (PDF No.80-1026), indicating that after sodium sulfide modification, FeS was successfully doped into the zero-valent iron particles during high-temperature pyrolysis.
[0066] 2. Effect of sulfur-modified iron-based biochar composites on the removal of trichloroethylene in aqueous solution
[0067] In this test example, trichloroethylene was selected as the characteristic pollutant and was divided into 28 groups, namely, a blank control group, Examples 1-25, and Comparative Examples 1-2. A shake bottle experiment was carried out by artificial water distribution to detect the removal effect of the biochar composite materials prepared in Examples 1-25 and Comparative Examples 1-2 on trichloroethylene. Among them, the blank control group did not add the biochar composite material in the experiment.
[0068] Shake flask test method Figure 4 As shown, the specific steps are as follows:
[0069] (1) Preparation of trichloroethylene solution: 13.74 μL of pure trichloroethylene solution was taken into a 1000 mL volumetric flask, 1.0 mL of methanol solution was added as a co-solvent, deionized water was added dropwise until the trichloroethylene was completely dissolved in the aqueous solution, deionized water was added to the 1000 mL mark, and the mixture was shaken to mix evenly to prepare a 20 mg / L trichloroethylene solution;
[0070] (2) The experiment used a 100 mL crimp bottle, the total solution volume was 100 mL, the material application ratio was controlled at 1 g / L, 0.1 g of the prepared biochar composite material was weighed and placed in the crimp bottle;
[0071] (3) Add 50 mL of the trichloroethylene solution and 50 mL of ultrapure water in step (1) to a 100 mL crimp bottle, seal it with a butyl rubber stopper, and oscillate in a constant temperature shaking incubator at 20° C. and 180 rpm for 72 h;
[0072] (4) 80 μL of the sample was placed in a 40 mL brown sample bottle filled with ultrapure water and the concentration of trichloroethylene (TCE) was tested using a purge and trap gas chromatography-mass spectrometer (GC-MS5977A; Agilent Technologies).
[0073] The experiment was repeated three times, and the results are shown in Table 4. Figure 5 As shown:
[0074] Table 4
[0075]
[0076]
[0077] From Table 4, Figure 5 We can get:
[0078] (1) The initial concentration of TCE is 20 mg / L. In the experiment, 50 mL of ultrapure water is added to 50 mL of TCE, which is 10 mg / L. TCE is volatile, and a blank control group is used to control volatilization. The removal rates of Examples 1-25 and Comparative Examples 1-2 are calculated based on the blank control (7 mg / L).
[0079] (2) In Table 4, in the step of impregnating the biomass material powder with the iron salt solution, the concentration range of the FeCl3·6H2O solution is 0.05 mol / L to 1.0 mol / L, and the rice straw powder: FeCl3·6H2O solution (g: mL) is 1 g: 10 mL to 1 g: 40 mL. The results show that when the concentration of the FeCl3·6H2O solution is higher than 0.3 mol / L and the dosage ratio of the rice straw powder: FeCl3·6H2O solution is higher than 1 g: 30 mL, the prepared sulfur-modified iron-based biochar slow-release composite material has a better effect on TCE removal.
[0080] (3) In Table 4, in the sulfur-modified iron-loaded biomass powder step, the concentration of the sodium acetate solution is 1 g / L to 5 g / L, the concentration of the sodium sulfide solution is 0.05 mol / L to 0.20 mol / L, and the amount of acetic acid added is 0.1 mL to 0.4 mL. The results show that when the sodium acetate solution is higher than 2.5 g / L, the concentration of the sodium sulfide solution is higher than 0.10 mol / L, and the amount of acetic acid added is 0.2 mL, the prepared sulfur-modified iron-based biochar slow-release composite material has a better effect on TCE removal.
[0081] (4) In Table 4, in the step of preparing sulfur-modified iron-based biochar by one-step carbon reduction method, the heating rate is 4℃ / min~6℃ / min, the temperature after heating is 800℃~900℃, and the holding time is 1h~4h. The results show that the heating rate has little effect on the TCE removal performance of the sulfur-modified iron-based biochar slow-release composite material. When the temperature after heating is higher than 800℃ and the holding time is greater than 2h, the prepared sulfur-modified iron-based biochar slow-release composite material has a better effect on TCE removal.
[0082] (5) Figure 5 In the comparative examples of TCE removal effects of different materials, the sulfur-modified iron-based biochar slow-release composite material prepared in Example 1 has a TCE removal rate of 94.86%, the rice straw biochar material prepared in Comparative Example 1 has a TCE removal rate of 50.43%, and the original rice straw material in Comparative Example 2 has a TCE removal rate of 1.00%. The results show that the sulfur-modified iron-based biochar slow-release composite material has the best TCE removal effect.
[0083] 3. Removal of trichloroethylene in aqueous solution by sulfur-modified iron-based biochar slow-release composite materials before and after aging
[0084] This test example selected trichloroethylene as the characteristic pollutant, and conducted a shake bottle experiment through artificial water distribution to detect the removal effect of sulfur-modified iron-based biochar slow-release composite materials on trichloroethylene. The experiment used a 100mL crimp bottle with a total solution of 100mL, which was divided into 2 groups: an experimental group and an aging group. Each group weighed 0.1g of the sulfur-modified iron-based biochar slow-release composite material prepared in Example 1 and placed it in a crimp bottle. The application ratio of each group of materials was controlled to be 1g / L. The specific test steps are as follows:
[0085] (1) Preparation of trichloroethylene solution: 13.74 μL of pure trichloroethylene solution was taken into a 1000 mL volumetric flask, 1.0 mL of methanol solution was added as a co-solvent, deionized water was added dropwise until the trichloroethylene was completely dissolved in the aqueous solution, deionized water was added to the 1000 mL mark, and the solution was shaken to mix evenly to prepare a 20 mg / L trichloroethylene solution for later use;
[0086] (2) Experimental group: 0.1 g of the sulfur-modified iron-based biochar slow-release composite material prepared in Example 1 was weighed and placed in a 100 mL crimp bottle, and then 50 mL of trichloroethylene solution and 50 mL of ultrapure water were added to the 100 mL crimp bottle, which was sealed with a butyl rubber stopper and shaken in a constant temperature shaking incubator at 20 °C and 180 rpm for 72 h;
[0087] (3) Aging group: 0.1 g of the sulfur-modified iron-based biochar slow-release composite material prepared in Example 1 was weighed and placed in a 100 mL crimp bottle, 100 mL of trichloroethylene solution was placed in a 100 mL crimp bottle, the bottle was sealed with a butyl rubber stopper, and the bottle was shaken in a constant temperature shaking incubator at 20°C and 180 rpm for 195 days for aging treatment; after the aging treatment, the sulfur-modified iron-based biochar slow-release composite material was taken out, dried at 80°C, and placed in a clean 100 mL crimp bottle, 50 mL of trichloroethylene solution and 50 mL of ultrapure water were added thereto, the bottle was sealed with a butyl rubber stopper, and the bottle was shaken in a constant temperature shaking incubator at 20°C and 180 rpm for 72 hours;
[0088] (4) Take the solutions in the crimp bottles of the experimental group and the aging group for testing. Take 80 μL of the solution and place it in a 40 mL brown sample bottle filled with ultrapure water. Use a purge and trap gas chromatography-mass spectrometer (GC-MS5977A, Agilent Technologies) to test the concentration of trichloroethylene. The removal effect is as follows: Figure 6 shown.
[0089] Depend on Figure 6It can be obtained that the test results for three consecutive days show that the newly prepared sulfur-modified iron-based biochar slow-release composite material (S-BC-nZVI-New) in Example 1 has a better removal effect on trichloroethylene than the sulfur-modified iron-based biochar slow-release composite material (S-BC-nZVI-Old) after aging for 195 days, indicating that aging in the solution will reduce the effect of the sulfur-modified iron-based biochar slow-release composite material. At the same time, after aging for 195 days, the removal rate of trichloroethylene by S-BC-nZVI-Old still reached 68.83%, 82.48% and 87.93%, which fully demonstrates that after sulfur modification, the iron-based biochar composite material has a slow-release function and can achieve long-term removal of chlorinated hydrocarbons in soil-groundwater.
[0090] In summary, the sulfur-modified iron-based biochar slow-release composite material provided by the present invention can efficiently remove trichloroethylene in groundwater. Moreover, after aging for 195 days, the sulfur-modified iron-based biochar slow-release composite material prepared by the present invention still has a very high trichloroethylene removal efficiency. It can be seen that the sulfur-modified iron-based biochar slow-release composite material provided by the present invention can effectively remove chlorinated hydrocarbons in groundwater for a long time.
[0091] In summary, although the embodiments of the present invention have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be construed as limitations on the present invention. A person skilled in the art can change, modify, replace and modify the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a sulfur-modified iron-based biochar slow-release composite material, characterized in that: The method comprises the following steps: (1) washing, drying, grinding and sieving agricultural waste in sequence to obtain biomass material powder; shaking the biomass material powder in an iron salt solution to obtain iron-loaded biomass material powder; (2) immersing the iron-loaded biomass material powder in a sodium acetate solution, adding acetic acid and sodium sulfide solution to obtain sulfur-modified iron-loaded biomass powder; (3) The sulfur-modified iron-loaded biomass powder is prepared into sulfur-modified iron-based biochar by a one-step carbon reduction method, that is, a sulfur-modified iron-based biochar slow-release composite material.
2. The method for preparing a sulfur-modified iron-based biochar slow-release composite material according to claim 1, characterized in that: The concentration of the iron salt solution is 0.05 mol / L to 1.0 mol / L; the iron salt in the iron salt solution is at least one of a trivalent iron salt and a divalent iron salt.
3. The method for preparing a sulfur-modified iron-based biochar slow-release composite material according to claim 2, characterized in that: The ratio of the biomass material powder to the iron salt in the iron salt solution in step (1) is 1 g: (0.5×10 -3 ~0.03)mol.
4. The method for preparing a sulfur-modified iron-based biochar slow-release composite material according to claim 1, characterized in that: The dosage ratio of the iron salt-loaded biomass material powder, the sodium acetate solution, the acetic acid solution, and the sodium sulfide solution is 1 g: (100-500) mL: (0.1-0.4) mL: (0.1-1.0) mL.
5. The method for preparing a sulfur-modified iron-based biochar slow-release composite material according to claim 4, characterized in that: The concentration of the sodium acetate solution is 1 g / L to 5 g / L; the mass fraction of the acetic acid solution is 36% to 38%; and the concentration of the sodium sulfide solution is 0.05 mol / L to 0.20 mol / L.
6. The method for preparing a sulfur-modified iron-based biochar slow-release composite material according to claim 1, characterized in that: The one-step carbon reduction method is specifically as follows: placing the sulfur-modified iron-loaded biomass powder in a tubular furnace into which high-purity nitrogen is continuously introduced, heating it and then keeping it warm, and then naturally cooling it to room temperature to obtain a sulfur-modified iron-based biochar slow-release composite material.
7. The method for preparing a sulfur-modified iron-based biochar slow-release composite material according to claim 6, characterized in that: The heating rate is 4°C / min to 6°C / min, the temperature after heating is 800°C to 900°C, and the insulation time is 1h to 4h.
8. The method for preparing a sulfur-modified iron-based biochar slow-release composite material according to claim 6, characterized in that: The flow rate of the high-purity nitrogen is 60 mL / min to 90 mL / min.
9. A sulfur-modified iron-based biochar slow-release composite material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8.
10. An application of a sulfur-modified iron-based biochar slow-release composite material, characterized in that: The sulfur-modified iron-based biochar slow-release composite material described in claim 9 is used to remove trichloroethylene from groundwater.
Citation Information
Cited By
Composite material for repairing cadmium pollution of farmland as well as preparation method and application of composite material
CN120325674A